How I created my own GPTs and how it is transforming my academic writing - Assis, Paulo de (2023)
This paper examines the transformative impact of bespoke GPT-4 models on academic writing workflows. By leveraging OpenAI’s user-friendly interface to create customized GPT models, tailored to specific needs and writing styles, the author experienced significant improvements in speed, diversity, and quality control of their writing. The custom model, trained on the author's extensive body of work, provided exceptional feedback, constructive criticism, and insightful suggestions, effectively acting as a highly capable personal assistant. The integration of these bespoke GPTs into the writing process allowed for a more balanced and reader-friendly output, reducing reliance on human feedback and enhancing the overall quality of academic writing. This study underscores the potential of personalized AI tools to revolutionize traditional writing methods and highlights the profound benefits of integrating AI into creative workflows.
FRIS
0
Keywords: MetamusicX:Transdisciplinary Encounters in and Beyond Music